Documenting Diaspora: Multiperspectivity in Sandhya Suri's Auto/Biographical Film "I for India" - Gabriele M. Linke (European Journal of Life Writing, 2014)
Yash Pal Suri, a young Indian doctor, went to the UK in 1965 to complete his medical training. He equipped himself and his family back in India with a camera, tape recorder etc. so that they could film episodes of their lives and exchange 'cine-letters,' which they did for about 40 years. In 2005, Suri's daughter, Sandhya Suri, created a 70-minute documentary from her family's filmed stories and other sources, selecting and arranging the various scenes and voices recorded and combining them with clips from historical TV programmes as well as interviews and short scenes filmed between 2003 and 2005 in India and England. She re-constructs her transnational family's life story as embedded it in a complex set of factors and influences. Sandhya' documentary is, on various levels, both biographical (hers of her family, and family members talking about each other) and autobiographical (her presence in the film and family members talking about themselves), and these perspectives are deeply entangled. By emphasising her family's failed attempt to re-settle in India, she complicates the story of cultural integration. The result is a reconstruction of this diasporic life narrative from various angles and along the various axes of diasporic relations, especially those with home (India) and the host society, describing the position of the diasporic subject as in-between and continuously shifting.